Capital Punishment in the Era of Globalization: A Partial Test of the Marshall Hypothesis Among College Students - LaChappelle, Levi (American journal of criminal justice, 2014)
U.S. Supreme Court Justice Thurgood Marshall’s hypothesis—that knowledge about the death penalty would reduce support for it—has been measured in terms of the public’s receptivity to key arguments for abolition including racial discrimination, lack of deterrent effect, and innocence. The effect of the international contextual argument, however, has gone virtually untested, despite the argument’s increased popularity. This preliminary study examines the impact of the international contextual argument against the death penalty on the opinion of 216 adult American students at a public university in California. The results of this study suggest that student support for the death penalty was decreased by exposure to international contextual information. The research presented in this paper is intended to encourage further investigation into the possibility that American public opinion may be significantly affected by international context.